Computed tomography coronary angiography with a 16-row multislice scanner: early experience and technical considerationse - Cademartiri, F.; Pavone, P. (Acta Biomedica Atenei Parmensis, 2004)
The visualization of coronary arteries has become possible only after the introduction of multislice CT scanners (MSCT), which allow a gantry rotation time of 500/ms, a number of 4 detector array, and an in-plane spatial resolution of 1 mm. Such spatial and temporal resolution has been recently improved with a new generation of MSCT scanners with 16 detector rows and a gantry rotation time of 420/ms.We report a preliminary experience with this new generation of scanners in a patient with coronary artery stent. Technical parameters are described with particular focus on the comparison with the past generation of 4-row MSCT scanners.